1998
DOI: 10.1007/s001340050642
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombin III in patients with severe sepsis

Abstract: The administration of AT III was safe and well-tolerated. It was followed by a 39 % reduction in 30-day all-cause mortality (NS). The reduction in mortality was accompanied by a considerably shorter stay in the ICU. Patients treated with AT III exhibited a better performance in overall severity of illness and organ failure scores (Acute Physiology and Chronic Health Evaluation II, multiple organ failure, organ system failure), which was noticeable soon after initiation of treatment. Patients treated with AT II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
5

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(43 citation statements)
references
References 38 publications
1
37
0
5
Order By: Relevance
“…However, in sepsis‐induced DIC, a decrease in AT activity is frequently observed27, 28, 29, 30 and is associated with high mortality rates 31, 32. Several RCTs to investigate the effects of high‐dose AT administration in patients with sepsis have been carried out 4, 33, 34, 35, 36. Although some RCTs indicated benefits of high‐dose AT administration in patients with sepsis,33, 34, 35 a large RCT (the KyberSept trial) failed to show any survival benefits 4.…”
Section: Antithrombinmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in sepsis‐induced DIC, a decrease in AT activity is frequently observed27, 28, 29, 30 and is associated with high mortality rates 31, 32. Several RCTs to investigate the effects of high‐dose AT administration in patients with sepsis have been carried out 4, 33, 34, 35, 36. Although some RCTs indicated benefits of high‐dose AT administration in patients with sepsis,33, 34, 35 a large RCT (the KyberSept trial) failed to show any survival benefits 4.…”
Section: Antithrombinmentioning
confidence: 99%
“…Several RCTs to investigate the effects of high‐dose AT administration in patients with sepsis have been carried out 4, 33, 34, 35, 36. Although some RCTs indicated benefits of high‐dose AT administration in patients with sepsis,33, 34, 35 a large RCT (the KyberSept trial) failed to show any survival benefits 4. However, a subgroup analysis of the KyberSept trial indicated that AT administration significantly improved survival rates in patients with sepsis‐induced DIC 9…”
Section: Antithrombinmentioning
confidence: 99%
“…Ketiga uji klinis menggunakan dosis AT III yang berbeda-beda. Dua uji klinis menggunakan dosis AT III yang rendah, yaitu uji klinis Eisele 4 dan uji klinis Schuster 4 sedangkan uji klinis lainnya, yaitu studi Fourrier dkk, 4 menggunakan dosis AT III yang tinggi.…”
Section: Hasil Penelusuranunclassified
“…Terjadinya KID dimulai dengan sitokin mengaktivasi jalur koagulasi secara sistemik sehingga terjadi consumptive coagulopati. 4 Usaha untuk menghentikan proses KID dengan suplementasi AT III sudah dimulai sejak sekitar tahun 1990 namun masih diperdebatkan baik dalam hal luaran dari penggunaan suplementasi tersebut, dosis penggunaan, interaksi dengan heparin, dan efek samping penggunaan. Antithrombin III adalah suatu glikoprotein rantai tunggal yang diproduksi oleh hati dan termasuk dalam serine protease inhibitor (SERPIN) superfamily.…”
Section: Pembahasanunclassified
“…23 A recently published paper on the meta-analysis of ATIII in severe sepsis demonstrated a clear trend towards increased survival. 24 However, some authors suggest that ATIII might have antiinflammatory as well as anti-DIC activity. 25 In the present study we induced a sepsis by the infusion of Salmonella abortus equi lipopolysaccharide into pigs; the development of systemic inflammation, coagulation activation and hemodynamic changes was followed over time.…”
mentioning
confidence: 99%